Using word analysis to track the evolution of emotional well-being in nineteenth-century industrializing Britain. Issue 4 (17th November 2021) - Lack, Pierre
Abstract: Happiness economics theorizes that economic growth is only tenuously connected to happiness. This article tests this theory on historical evidence by quantifying the trend in emotional well-being (EWB) of British men during the period of rapid industrialization between 1800 and 1900, using a digitized corpus of 19, 682 pamphlets published in Britain during this period and held by JSTOR. EWB is measured between these years using a sentiment analysis method of quantifying the frequency over time of a set of positive-valence ("happy") word groups relative to negative-valence ("sad") word groups in the corpus, finding that it remains trendless throughout. This method thereby also provides insight into the quality of life of men during the Industrial Revolution.